The relationship between well-being, social engagement, and the role of the state in realizing civic happiness - Fahmi, Rizal; Suryadi, Karim (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Happiness is an important aspect of a country's life, even in the study of public policy making happiness the main goal. Happiness comes from internal factors that come from personal motivation and motivation for something, while external factors come from various conditions outside of oneself, the focus in this research is external factors (such as government public policy). The problem of making public policy only limited to political decisions results in neglecting the happiness of citizens. This research aims to examine social aspects based on various previous studies that have contributed to citizen happiness. This research uses a qualitative approach with literature studies, materials derived from journals and books are the main sources used as units of analysis. The results show that social aspects, such as population, welfare, religion, social capital, and social engagement have an impact on happiness. Creating public space in developing various social aspects is an important thing that needs to be done so that citizens have broad access to develop themselves and feel happiness in the public space created by the state.